006.1 The efficacy of pristinamycin for mycoplasma genitalium – an increasing multidrug resistant pathogen. (13th September 2015) - Bradshaw, CS; Twin, J; Bissessor, M; Read, TRH; Jensen, JJ; Fairley, CK; Garland, SM; Chen, MY; Worthington, K; Grant, M; Tabrizi, SN
Abstract : Introduction: To determine the efficacy of pristinamycin-based regimens for M. genitalium -infections failing prior regimens and to examine the presence of 23S rRNA and ribosomal protein gene mutations and their association with treatment failure. Methods: In 2013 M. genitalium -infected men and women attending Melbourne Sexual Health Centre who failed azithromycin and moxifloxacin were treated with pristinamycin 1g qid for 10 days with a test-of-cure (TOC) 3–4 weeks post-pristinamycin. From December 2014 pristinamycin was prescribed 1g bid for 10 days second-line following azithromycin failure. Pre- and post-treatment samples were stored and sequenced to detect 23S rRNA and ribosomal protein gene mutations, as potential markers of pristinamycin resistance. Results: By March 2015 37 M. genitalium -infected patients had received pristinamycin: 32 males (10 rectal; 22 urine samples) and 5 females (1 rectal; 3 urine; 1 cervical). TOC data are available on 25 patients at abstract submission: 20 were cured (80%; 95% CI 61–92%) and 5 (20%; 8–39%) failed pristinamycin. Failure rates in the 16 patients treated with 1g qid 10 days were 12% (n = 2), and 33% (n = 3) in the 9 treated with 1g bd 10 days, p = 0.23. Of the 5 pristinamycin failures; 2 were cured with moxifloxacin, 3 failed moxifloxacin and are awaiting TOCs following solithromycin or combined doxycycline/pristinamycin. Mutations in 23S rRNA and ribosomal protein genes were associated with failure of pristinamycin. Conclusion: Increasing reports of azithromycin and moxifloxacin failure for M. genitalium -infections necessitates evaluation of new agents. We present some of the earliest data on the use of pristinamycin for M. genitalium . Treatment failure occurred when delivered as monotherapy following failure of prior regimens. Current data on use of combined pristinamycin and doxycycline as a second line regimen after azithromycin failure will be available for presentation. Resistance mutations in the 23S rRNA and ribosomal protein genes are associated with pristinamycin failure. Disclosure of interest statement: No pharmaceutical grants were received in the development of this study.